2019
DOI: 10.1038/s41375-019-0582-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo efficacy of mutant IDH1 inhibitor HMS-101 and structural resolution of distinct binding site

Abstract: Mutations in isocitrate dehydrogenase 1 (IDH1) are found in 6% of AML patients. Mutant IDH produces R-2-hydroxyglutarate (R2HG), which induces histone-and DNA-hypermethylation through inhibition of epigenetic regulators, thus linking metabolism to tumorigenesis. Here we report the biochemical characterization, in vivo antileukemic effects, structural binding and molecular mechanism of the inhibitor HMS-101, which inhibits the enzymatic activity of mutant IDH1 (IDH1mut). Treatment of IDH1mut primary AML cells r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Thus, careful baseline assessment of cardiovascular risk factors and genetic risk factors including the IDH mutation status as well as baseline measurement of cardiac function by a cardio-oncology specialist team should be performed in these AML patients (especially when adjuvant anthracyclines are used). It will be interesting whether IDH inhibitors, that effectively reduce R-2HG levels in vivo, can reduce the cardiovascular risk observed in our study [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, careful baseline assessment of cardiovascular risk factors and genetic risk factors including the IDH mutation status as well as baseline measurement of cardiac function by a cardio-oncology specialist team should be performed in these AML patients (especially when adjuvant anthracyclines are used). It will be interesting whether IDH inhibitors, that effectively reduce R-2HG levels in vivo, can reduce the cardiovascular risk observed in our study [42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…It will be interesting whether IDH inhibitors, that effectively reduce R-2HG levels in vivo, can reduce the cardiovascular risk observed in our study. 42 46 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported the characterization of HMS-101 a new IDH1 inhibitor with the peculiar property to interact with the active site of IDH1 -mutant in close proximity to the regulatory segment of the enzyme [ 175 ]. The inhibitor exerted a potent anti-leukemic effect on mutant IDH1 leukemia models; interestingly, leukemic cells treated with this inhibitor showed a marked upregulation of the transcription factors CEBPA and PU.1 and a decrease of cyclin A2 [ 175 ].…”
Section: New Idh Inhibitors Under Evaluationmentioning
confidence: 99%
“…BAY1436032 is an oral small-molecule inhibitor of mIDH1 that is active in preclinical models of mIDH1 cancer [ 15 17 ]. Most mIDH1 inhibitors, including BAY1436032, reportedly interact with an allosteric site on the mutant enzyme, although an inhibitor which interacts directly with the active site was recently described [ 18 ]. Preclinical experiments focusing on mIDH1 AML found that BAY1436032 inhibits R-2HG production and colony growth in vitro , while promoting leukemic blast clearance, myeloid differentiation, and survival in animal models [ 16 ].…”
Section: Introductionmentioning
confidence: 99%